Implementasi Kurikulum Merdeka di SD - Heliwasnimar Heliwasnimar; Henny Hamdani Basri; Fadriati Fadriati (Departement of Mathematics Education, 2024)
The Merdeka Curriculum, launched by the Ministry of Education and Culture in 2022, brings a new paradigm to Indonesian education. Its implementation in Elementary Schools (SD) is focused on developing character, literacy, skills, technology, and strengthening the Pancasila Student Profile. This article examines the Implementation of the Independent Curriculum in Elementary Schools, discussing Learning Achievements, Learning Objectives, Flow of Learning Objectives, Teaching Modules, the Project for Strengthening Pancasila Student Profiles, supporting and inhibiting factors, policies and strategies for implementing the independent curriculum. This article aims to describe the implementation of the independent curriculum in elementary schools. This research is library research and is included in the descriptive qualitative research approach